Sobre Steven Topik, Carlos Marichal y Zephyr Frank (eds.), From Silver to Cocaine. Latin American Commodity Chains and the Building of the World Economy, 1500-2000 - Hausberger, Bernd (Historia Mexicana, 2008)
-